PENGARUH LATIHAN FARTLEK DENGAN PENINGKATAN CARDIOVASCULAR ENDURANCE PADA ATLET FUTSAL JALLORO KABUPATEN KOLAKA UTARA SULAWESI-TENGGARA - Sulaeman; Resky Ana Abadi; Ika Sartika; Basman (Universitas Halu Oleo, 2022)
Based on the observations of researchers on Jalloro futsal athletes where researchers are still active and join the team, there still many players who have low cardiovascular endurance. Where in the last few matches the Jalloro team failed to win because they could not maintain their advantage, this was due to decreased cardiovascular endurance at the end of the match. Based on these problems, the researchers chose to conduct a study to dertemine the effect of fartlek training on increasing heart endurance for athletes in Jalloro futsal Kolaka Utara regency Southeast Sulawesi. This research is impure experimental research. This research was conducted with 17 subjets, who are athletes, still active and have joined the coaching and training program by the Jalloro futsal tim coaching team. The instrument used in this study was the VO2max endurance test with Balke Method. To analyze the research using T-Test, namely by comparing the results of the Pretest and Posttest in the experimental group. Based on the results of statistical tests, it was obtained that the T-Test value between the pretest and posttest farlek exercises the increase in cardiovascular endurance which had value of 5,197, p = 0,000, because p = < 0,05, there was a significant increase. Jugging from the average value, the pretest average value = 29,4241 the posttest average value = 33,1429 because the posttest value is greater than prestest average value, there is a increase in cardiovascular endurance by = 3,1429 or 12,64 %.